Pengaruh Kandungan CaCO3 dicuci dan tanpa dicuci Terhadap Kuat Tekan Beton di Pantai Pulau Mandangin - Vikki Ariyanto, Sandy; Joni, Idon (Pendidikan Fisika, FKIP, Universitas Nahdlatul Ulama Cirebon, 2023)
Indonesia is one of the countries with abundant natural resource wealth including oil, gas and other natural mineral materials. One of the natural mineral materials found on Mandangin Island, Sampang Regency is CaCO3. The purpose of this research is CaCO3 as a substitute for iron sand in concrete mixtures with a variety of places, namely the hamlets of the west and east coasts. To find out the quality of the concrete mixture, an XRF test and a compressive strength test were carried out and compared the CaCO3 mixture which went through the washing and unwashed processes. The results of the XRF test showed that the highest content of the mineral Calcium (Ca) was in the East Coast hamlets of 94.88% and 94.73% in the West Coast. Whereas for the compressive strength test for washed and unwashed variations the highest value was in the washed variation with the highest value level being in the east coast hamlet of 231.17 Kg/Cm2 and west of 176.78 Kg/Cm2. This is a recommendation that CaCO3 sand can be used as a concrete mixture